Insurance Coverage for Emerging Diabetes Technologies: Payers' Perspective - Nolan, Tim; Frazzitta, Marie (Diabetes technology & therapeutics, 2021)
Advances in glucose monitoring and insulin delivery technologies have led to the development of innovative self-management tools, such as continuous glucose monitoring, automated insulin delivery systems, and smart connected insulin pens. Although the clinical advantages of today's emerging diabetes technologies are well documented, the cost of integrating these tools into clinical practice must be considered to sustain the financial viability of both public and private insurers. Most clinicians are unfamiliar with the process the commercial insurers follow when making these decisions. This article reviews the key factors the insurers consider when determining eligibility criteria.